Religious Pluralism, the Nondelegation Rule, and Fulton v. Philadelphia - Emily R. Gill (Religions, 2025)
In Fulton v. City of Philadelphia, the United States Supreme Court ruled that the city of Philadelphia could not exclude a Catholic Social Services agency from the city’s foster care system because it would not work with same-sex couples. Access to foster care agencies, however, is a public benefit that should not involve religious qualifications interposed by a nongovernmental organization. When aided by public funds, religious organizations should not receive exemptions from nondiscrimination laws to deny potential clients services because they disagree with these clients’ religious beliefs, sexual orientations, or marital status. First, equal access to public funds is not neutral when it allows religious entities to limit the life plans of others who do not share their convictions. Second, religious entities should certainly be able to advance religion but not on the public dollar. Finally, although exemptions for these entities augment the free exercise of religion, especially when accompanied by public funds, they also amount to what has been termed a “shadow establishment”.